Hair & hair growth - Tobin, Desmond J. (Henry Stewart Talks, 2014)
Biologic value of hair, Hair follicle as a ‘mini-organ’, Hair fiber structure and function, Hair follicle morphogenesis, Hair follicle as a regenerative tissue, Hair follicle as an neuroendocrine tissue, Hair pigmentation, Hair growth disorders including alopecia areata and androgenetic alopecia